1962
DOI: 10.1002/aic.690080307
|View full text |Cite
|
Sign up to set email alerts
|

The flow of rarefied gases

Abstract: It has been shown experimentally by Knudsen and others that gases flowing a t decreasing total pressures through small capillaries pass from a region of Poiseuille flow to a so-called slip flow region which contains a flow minimum. Frequently the practice has been followed of approximating this behavior with a linear relationship which, although it gives a fairly good approximation to the actual curve, is incomplete in theory. Some discussion of the use of this equation in the design of vacuum piping and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…18 In transport where viscous effects dominate, it has been observed that the transport coefficient generally increases with density, after a small decrease at transition-regime densities. 1,5,6 This increasing trend has also been observed in methane transport in silica mesopores, 16,17 and the results depicted in Fig. 4 are consistent with these findings, in the wider pores.…”
Section: A Simulation Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…18 In transport where viscous effects dominate, it has been observed that the transport coefficient generally increases with density, after a small decrease at transition-regime densities. 1,5,6 This increasing trend has also been observed in methane transport in silica mesopores, 16,17 and the results depicted in Fig. 4 are consistent with these findings, in the wider pores.…”
Section: A Simulation Resultssupporting
confidence: 87%
“…In order to permit momentum exchange between the solid and the fluid parallel to the walls, diffuse boundary conditions were applied. 35 Data were obtained by averaging results from runs of length 2ϫ10 6 time steps, each beginning from distinct initial conditions. For each run, averages were collected only after the system had been allowed to relax to equilibrium or the steady state ͑over approximately 40 000 time steps͒.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…He assumed that the total gas transport in a long capillary is given at all pressures by the addition of (1) G) • EXPERIMENTAL DATA [19].…”
Section: Transition Flowmentioning
confidence: 99%
“…The above equation (18), in the same form as equation (10), is (19) If the Lund and Berman equations are considered as differential equations and (AP1/L) + (dP1/dx) and (A~/L) + (dP/dx), then there are only two significant differences between equations (10) and (19). The coefficient of .the second term is smaller for the GCM than for PBM and is the primary source of the differences in the calculated separation efficiencies for the same long capillary.…”
Section: General Capillary Model (Gcm)mentioning
confidence: 99%